Eksistensi Islamic Full Day School: Analisis Persepsi Dan Aspirasi Masyarakat Pada SD Kota Jayapura - Firdaus, Muhammad Anang (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This paper describes the existence of an Islamic full-day school in Jayapura City based on community perceptions and aspirations. This research is descriptive-analytical using the snowball sampling technique. Data were collected through observation, interviews, and documentation. The results show that the Islamic full-day school in Jayapura City is a private educational institution that implements a full-day school system. The curriculum implements a combination of general and religious material, as well as flagship activity programs. The management is professional, new, and has a high work ethic. Moreover, it has expensive costs and representative facilities. In people's perceptions, this institution combines general and religious materials, has expensive costs with very representative facilities, and has excellent programs, especially in religiousness. Therefore, it is considered necessary. Nevertheless, there is also a view that Islamic full-day school is not necessary because it is considered only for the upper-middle-class economy; long learning causes children to be bored, saturated, physically weak, and unconcentrated, as well as have negative consequences for children. The Islamic full-day school model, which has good quality based on community expectations, is an Islamic full-day school that is well-managed and more professional with affordable costs by cooperating with the government, parents, and donors in order that it can be enjoyed by all groups. Development and improvement of the quality of professional teachers and staff who are in their fields and better facilities and programs.